An Exploring Class Conflict in Samira Sedira's People Like Them through Lewis Coser's Theory - Febriani, Silviana Berly; Ambar Andayani (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2024)
This study discusses the class conflict that occurs in Samira Sedira’s People Like Them. The aim of this research is to describe the forms of class conflict and tells the factors that cause the class conflict find in the Samira Sedira’s People Like Them. The researcher chooses this novel because Sedira explores the issue of class conflict through two families who live in a village at the foot of the mountain. The researcher uses a qualitative descriptive method and a sociological approach to connect social conflict and literature. To analyze the conflict in the novel, the researcher uses Lewis Coser’s Class Conflict theory. Coser's theory emphasizes that class conflict can drive social change and maintain social structure by enabling tensions in society. The researcher finds two forms of class conflict, namely Realistic and Non-realistic conflict, and the factors that cause class conflict are Social and economic Enviousness, Cultural Differences and Assimilation, Exclusion and Racism, and the last one is Economic Injustice and Insecurity. This conflict is reflected in various aspects of their lives, including employment, housing, and daily social interactions. The study concludes that "People Like Them" not only highlights issues of class conflict in the specific context of the society depicted in the novel, but also offers broader insights into social dynamics relevant to Coser's theory of class conflict.Keywords: class conflict, cause of class conflict, non-realistic conflict, realistic conflict